A hospital-based cross-sectional study on congenital anomalies in newborn babies of Uttarakhand - Shirke, Rupali; Rawat, Anil; Chander, Vipan; Gupta, Alpa (Indian Journal of Child Health, 2016)
Background: Congenital anomalies make an important contribution to infant mortality. They remain a leading cause of death in many countries of the world. The prevalence and pattern of presentation vary from place to place. Objective: The aims and objectives of this study were to determine the prevalence of congenital abnormalities among babies (inborn and outborn) admitted at the Himalayan Hospital, Dehradun, Uttarakhand, India. Materials and Methods: A cross-sectional retrospective study was conducted in a Medical College Hospital in Uttarakhand. The case files of these babies were retrieved from the hospital records department and examined individually by the investigators. Data collection was done with structured forms designed for the study. Result: Among total 2242 neonates included in the study, the prevalence of congenital malformations was 8.3%. Central nervous system and cardiovascular, musculoskeletal, and genitourinary systems were found to be most commonly involved. Conclusion: The present study provides us an idea regarding prevalence of cases of congenital malformations and factors affecting it. In Indian environment, this study helps us to know the pattern of congenital malformation in this part of the country.